Analisis Efektivitas Kinerja Mesin Lohia 1 Jumbo Bag di PT. XYZ - Febrian Akbar Primadha; Siti Muhimatul Khoiroh (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
PT. XYZ is a manufacturing factory that uses a Lohia 1 Jumbo Bag machine to produce plastic sacks. This machine often encounters problems during operation due to maintenance that is still reactive (Run-to-Failure), which causes a lot of unplanned downtime. This study aims to evaluate the actual operational performance of the machine and propose the technically and economically best preventive maintenance schedule. The research methodology begins by combining the Overall Equipment Effectiveness (OEE) approach and Six Big Losses to determine the level of efficiency and identify the main causes of time wastage in the production line.